BUSINESS PLAN : UD Fruiti â U - Wijaya, Jeany Oktavia (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Business plan aims to determine the feasibility of opening a food and beverage business, named UD Fruiti â U. Itâs inspired by the healthy lifestyle that began intensively in the community . The business concept is designed online store with products such as processed fruit juices in the form Jelly. The funds required to start this business is Rp 100.000.000,00 (One Hundred Million Rupiah). Based on the result of the feasibility study, a business plan is feasible accepted with NPV of Rp 66.186.679,00, IRR of 96%, and the DPP for 3 years and 25 days.